When is epistemic dependence disvaluable?. (21st April 2021) - Gaultier, Benoit
Abstract: There clearly seems to be something problematic with certain forms of epistemic dependence. However, it has proved surprisingly difficult to articulate what this problem is exactly. My aim in this paper is to make clear when it is problematic to rely on others or on artefacts and technologies that are external to us for the acquisition and maintenance of our beliefs, and why. In order to do so, I focus on the neuromedia thought experiment. After having rejected different ways in which one might want to capture the intuition in question, I argue that this device deprives us of understanding and therefore of the most valuable epistemic good. I then address the question of whether the moral of the story is that we should not develop, be equipped with, or use devices such as the neuromedia.